Morphological Root Responses and Molecular Regulation of Cation Transporters Are Differently Affected by Copper Toxicity and Cropping System Depending on the Grapevine Rootstock Genotype - Marastoni, Laura; Sandri, Michele; Pii, Youry; Valentinuzzi, Fabio; Cesco, Stefano; Mimmo, Tanja (Frontiers in Plant Science, 2019)
The high copper (Cu) concentration in vineyard soils causes the increase of Cu toxicity symptoms in young grapevines. Recently, intercropping of grapevine and oat was shown to reduce Cu toxicity effects, modulating the root ionome. On these bases, the focus of the work was to investigate the impact of Cu toxicity of either monocropped or oat-intercropped grapevine rootstocks plants (196.17 and Fercal), at both phenotypic (i.e. root architecture) and molecular (i.e. expression of transporters) levels. The results showed a different response in terms of root morphology that are both rootstock- and cropping system dependent. Moreover, the expression pattern of transporter genes (i.e. VvCTr, VvNRAMP and VvIRT1) in monocropped grapevine might resemble a Mn deficiency response induced by the excess of Cu, especially in Fercal plants. The gene expression in intercropped grapevines suggested rootstock-specific response mechanisms, depending on Cu levels. In fact, at low Cu concentrations, Fercal enhanced both root system growth and transporter genes expression; contrarily, 196.17 increased apoplast divalent cations accumulation and transporters expression. At high Cu concentrations, Fercal increased the expression of all bivalent cation transporters and, as previously observed, enhanced the release of root exudates, whereas the 196.17 only modulated transporters. In conclusion, our results might suggest that the different adaptation strategies of the two rootstocks to Cu toxicity could be mainly ascribable to a fine-tuning of bivalent cations transporters expression at root level.